Synthesis of hybrid silicates containing porphyrins incorporated by a sol-gel process and their properties - Biazzotto, J. C.; Sacco, H. C.; Ciuffi, K. J.; Neri, C. R.; Ferreira, A. G.; Iamamoto, Y.; Serra, O. A. (Elsevier B.V., 1999)
Porphyrin was incorporated in a silicate network, via a covalent bond, by grafting a functional group with 3-aminopropyltriethoxysilane, using a sol-gel process. We have carried out the synthesis and measured the absorption spectra, nuclear magnetic resonance spectra, infrared (IR) spectra, luminescence spectra and lifetime of these hybrid silicates, porphyrinosilicas. These samples contained the following free-base porphyrins: meso-tetrakis-p-chlorobenzoylporphyrin, meso-tetrakis-2,6-dichloro-3-chlorosulfonylphenylporphyrin. The obtained porphyrinosilicas have similar absorption and luminescence spectra to the free base porphyrins in solution. IR spectra confirm the formation of monomeric species. Lifetime measurement for porphyrinosilica reveals that 32% +/- 2% of porphyrin is covalently bonded to the silica network. (C) 1999 Elsevier B.V. B.V. All rights reserved.